Implementation Of Permenkumham No. 40 Of 2017 Concerning Guidelines For Organizing Food For Prisoners In Class IIa Cibinong Correctional Institutions - Lesmana, Topan; Hartini, Sri; Purwaningsih, Prihatini (JURNAL MAHASISWA YUSTISI, 2024)
This study aims to determine how the implementation of the SOP for organizing food for prisoners in accordance with Permenkumham No.40 of 2017 at Class IIA Cibinong Correctional Facility. This research applies the Yuridis Empiris type of research, which is an approach that combines legal aspects (juridical) and empirical aspects (based on observations or empirical data). then the problem approach used is a qualitative approach, which means an approach in research that prioritizes the collection and analysis of data in the form of text, images, or sounds resulting from observations, interviews, in Cibinong Class IIA Prison. Based on the results of the study, it shows that, namely (1) the implementation of the SOP for organizing food for and inmates at Class IIA Cibinong Correctional Facility is in accordance with Permenkumham No.40 of 2017, the SOP is: agreement letter, request for food ingredients, receipt of food ingredients, storage of food ingredients, processing of food ingredients, serving food, distributing food, sanitation and environmental health of the kitchen. (2) The inhibiting factors faced by Class IIA Cibinong Correctional Institution are time management factors, natural factors and human resource factors. Time management factors include: Logistics and distribution problems, prisoners exceeding the predetermined capacity (new prisoners). Natural resource factors include: Limited number of workers, employee instability, health problems. Natural factors include: Natural Disasters, Extreme Weather Changes, Disturbances in Natural Resources